2006
DOI: 10.1038/modpathol.3800586
|View full text |Cite
|
Sign up to set email alerts
|

Cellular retinol binding protein-1 expression in endometrial hyperplasia and carcinoma: diagnostic and possible therapeutic implications

Abstract: Cellular retinol binding protein-1 (CRBP-1) contributes to the maintenance of the differentiative state of endometrial glandular cells through the regulation of bioavailability of retinol and derivatives, but its role in endometrial oncogenetic process remains unclear. Antibodies to CRBP-1, estrogen and progesterone receptors (ER and PR) were applied to paraffin sections of proliferative (n ¼ 10) and secretory endometrium (n ¼ 9), and to endometrial polyps (n ¼ 6), simple (n ¼ 7), complex (n ¼ 3) and atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…They have been shown to inhibit the growth of human cancer cells in vitro [40], and to be effective chemopreventive and chemotherapeutic agents in ovarian and in other human epithelial and hemotopoietic tumors [41]. A reduction of RPB-1 gene expression has already been reported in breast [42], endometrial [43] and ovarian carcinoma [44], suggesting that a reduction of RBP-1 expression may significantly contribute to the oncogenic process, through altering the vitamin A metabolism. While the reduction of RBP-1 expression is reported in less differentiated endometrial carcinomas, it has been demonstrated that in breast [45] and serous ovarian tumors [44], its reduction appears to be associated with early stage carcinogenesis process: a correlation with tumor stage and grade has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown to inhibit the growth of human cancer cells in vitro [40], and to be effective chemopreventive and chemotherapeutic agents in ovarian and in other human epithelial and hemotopoietic tumors [41]. A reduction of RPB-1 gene expression has already been reported in breast [42], endometrial [43] and ovarian carcinoma [44], suggesting that a reduction of RBP-1 expression may significantly contribute to the oncogenic process, through altering the vitamin A metabolism. While the reduction of RBP-1 expression is reported in less differentiated endometrial carcinomas, it has been demonstrated that in breast [45] and serous ovarian tumors [44], its reduction appears to be associated with early stage carcinogenesis process: a correlation with tumor stage and grade has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…High-mobility group-B1 (HMGB1), CD3, CD19, and F4/80 protein expression was performed by immunohistochemistry (32) on 4-mthick paraffin sections using antibodies from Abcam. The positive immunostaining was assessed using a semiquantitative scale modified as follows: 3, strong; 2, moderate; 1, weak; 0, absent (30). Measurements were performed by two different investigators in at least 10 fields at ϫ200 magnification for each case, with an inter observer variability of Ͻ5%.…”
Section: Methodsmentioning
confidence: 99%
“…Semi-quantitative evaluation of IDE immunoreaction was estimated at 200ϫ magnification in at least 10 fields by two of the authors, who used a grading system in arbitrary units (a.u.) as follows: negative ϭ 0; Ͻ25% of cells weakly positive ϭ 0.5; diffuse weakly positive ϭ 1; moderately positive ϭ 2 and strongly positive ϭ 3 (26). The results were expressed as mean number Ϯ S.E., with an interobserver reproducibility of Ͼ95%.…”
Section: Shsy5y Stimulation With All Trans Retinoic Acid (Atra)-shsy5mentioning
confidence: 99%
“…As a control for the tumors of the nervous system, we used paraffin sections of bioptic material, which contained small fragments of non-neoplastic cerebral tissue that had been removed during the surgical excision of benign tumors (n ϭ 4). For the immunohistochemical procedure (26), serial 4-m-thick paraffin sections were stained with hematoxylin/eosin or used for immunohistochemistry. Regarding the latter, we performed deparaffinization, blocking of endogenous peroxidase activity with 0.2% H 2 O 2 (20 min) and incubation with normal goat serum (30 min).…”
Section: Shsy5y Stimulation With All Trans Retinoic Acid (Atra)-shsy5mentioning
confidence: 99%